Peripheral regulatory cells immunophenotyping in Primary Sjögren's Syndrome: a cross-sectional study - Furuzawa-Carballeda, Janette (BioMed Central, 2013)
INTRODUCTION: IL-10--producing B cells, Foxp3-expressing T cells (Tregs) and the IDO-expressing dendritic cells (pDC) are able to modulate inflammatory processes, to induce immunological tolerance and, in turn, to inhibit the pathogenesis of autoimmune disease. The aim of the study was to characterize and to enumerate peripheral IL-10--producing B cells, Tregs and pDCregs in primary Sjögren's Syndrome (pSS) patients in regard of their clinical and serologic activity. METHODS: Fifty pSS patients and 25 healthy individuals were included in the study. CD19(+)--expressing peripheral B lymphocytes were purified by positive selection. CD19(+)/CD24(hi)/CD38(hi)/IL-10--producing B cells, CD4(+)/CD25(hi)/Foxp3(+ )and CD8(+)/CD28(-)/Foxp3(+ )Tregs, as well as CCR6(+)/CD123(+)/IDO(+ )DCs, were quantitated by flow cytometry. RESULTS: Immature/transitional circulating IgA(+ )IL-10--producing B cells had higher levels in pSS patients versus control group, whereas CD19(+)/CD38(hi)/IgG(+)/IL-10(+ )cells had lower percentage versus control. Indeed CD19(+)/CD24(hi)/CD38(hi)/CD5(+)/IL-10(+), CD19(+)/CD24(hi)/CD38(hi)/CD10(+)/IL-10(+), CD19(+)/CD24(hi)/CD38(hi)/CD20(+)/IL-10(+), CD19(+)/CD24(hi)/CD38(hi)/CD27(-)/IL-10(+), and CD19(+)/CD24(hi)/CD38(hi)/CXCR7(+)/IL-10(+ )cells had higher frequency in clinical inactive pSS patients when compared with control group. Remarkably, only percentages of CD19(+)/CD24(hi)/CD38(hi)/CD10(+)/IL-10(+ )and CD19(+)/CD24(hi)/CD38(hi)/CD27(-)/IL-10(+ )subsets were increased in pSS serologic inactive versus control group (P < 0.05). The percentage of IDO-expressing pDC cells was higher in pSS patients regardless of their clinical or serologic activity. There were no statistically significant differences in the percentage of CD4(+)/CD25(hi)/Foxp3(+ )Tregs between patient groups versus controls. Nonetheless, a decrease in the frequency of CD8(+)/CD28(-)/Foxp3(+ )Tregs was found in inactive pSS patients versus controls (P < 0.05). CONCLUSIONS: The findings of this exploratory study show that clinical inactive pSS patients have an increased frequency of IL-10--producing B cells and IDO-expressing pDC cells.